(3eTcd GdbQBf GdYRjRs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdaGJMI s
(3BNQgG (B:s
(3hGNJGQ GdReNTQi GdhLg GdChd hbGd eG CMb Cf GSe GdfGS jfWdb Ydi GdLf GdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs